2020
DOI: 10.1038/s41598-020-59582-3
|View full text |Cite
|
Sign up to set email alerts
|

Biocarbon from peanut hulls and their green composites with biobased poly(trimethylene terephthalate) (PTT)

Abstract: There are millions of tons of post-food processing residues discarded annually. Currently, these waste materials are discarded to landfill, used as animal feed or incinerated. This suggests that there are potential uses for these materials in value-added applications. This work focuses on the characterization and valorization of peanut hulls through the generation of green composites. Peanut hulls were pyrolyzed at 500 °C and analyzed to discover their unique surface morphology and relatively low ash content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 64 publications
(94 reference statements)
1
31
0
Order By: Relevance
“…Another interesting study, reported by Picard and co‐workers, [ 145 ] was the recycling of peanut hulls to obtain biocarbon by pyrolysis that was used as fillers in poly(trimethylene terephthalate) composites. The waste incorporation seemed to increase flexural and tensile modulus as well as it contributed for a sustainable product development.…”
Section: Municipal Solid Wastesmentioning
confidence: 99%
“…Another interesting study, reported by Picard and co‐workers, [ 145 ] was the recycling of peanut hulls to obtain biocarbon by pyrolysis that was used as fillers in poly(trimethylene terephthalate) composites. The waste incorporation seemed to increase flexural and tensile modulus as well as it contributed for a sustainable product development.…”
Section: Municipal Solid Wastesmentioning
confidence: 99%
“…The biocarbon structure has some hygroscopic tendencies due to its high porosity. Even after applying the drying procedure, the moisture content of the material is still about 1%, while before drying, is usually around 7-10% [78,79]. The presence of moisture may lead to the increased intensity of hydrolytic degradation phenomena, which were observed for polycarbonate/biocarbon (PC/BC) composites [54].…”
Section: Rheological Characteristic-small Amplitude Oscillation Shearmentioning
confidence: 99%
“…It is a multifunctional platform for material science [ 23 ], as Mohanty and co-workers [ 24 ] clearly demonstrated for the production of performing composites. In the very same field, biochar has been proved to be a surprising and versatile filler able to improve the mechanical [ 25 , 26 ], thermal [ 27 , 28 , 29 ] and electrical [ 30 , 31 , 32 ] properties of plenty of the polymeric matrix. The strength of biochar is the high productive flexibility that improves its cost-effectiveness balancing the material properties with biomass streams availability.…”
Section: Introductionmentioning
confidence: 99%